Vers une conception de l’élève-sujet : la relation enseignant-élève en dispositif relais - Maël Virat (Éducation et Socialisation)
The dispositifs relais take in secondary school pupils at risk of school dropout and social marginalisation. It is relevant to wonder how the specialized teachers deal with these young people who already put educational institutions in a difficult situation. The concept of pupil-subject, although implicit in the teachers’discourse, highlights the recognition of the thoughts and feelings of the pupils. On the basis of the subject/object opposition and by examining through twelve talks how the teachers conceive their relation with the pupil and how they take into account his emotional needs, this text gives a definition of the concept of pupil-subject, based on the acceptance to establish an affective relationship with the pupils. In conclusion, the speech of the teachers, because it grants a place to a pupil-subject, could be close to the concept of unconditional positive regard.